A Note on Conservation Laws of Symplectic Difference Schemes for Hamiltonian Systems (Journal of Computational Mathematics, 1991)
In this paper we consider the necessary conditions of conservation laws of symplectic difference schemes for Hamiltonian systems and give an example which shows that there does not exist any centered symplectic difference scheme which preserves all Hamiltonian energy.